Biochemical Characterization of a Novel Monospecific Endo-β-1,4-Glucanase Belonging to GH Family 5 From a Rhizosphere Metagenomic Library - Wierzbicka-Woś, Anna; Henneberger, Ruth; Batista-García, Ramón Alberto; Martínez-Ávila, Liliana; Jackson, Stephen A.; Kennedy, Jonathan; Dobson, Alan D. W. (Frontiers in Microbiology, 2019)
Cellulases have a broad range of different industrial applications, ranging from food and beverages to pulp and paper and the biofuels area. Here a metagenomics based strategy was used to identify the cellulolytic enzyme CelRH5 from the rhizosphere. CelRH5 is a novel monospecific endo-β-1,4-glucanase belonging to the glycosyl hydrolase family 5 (GH5). Structural based modelling analysis indicated that CelRH5 is related to endo-β-1,4-glucanases derived from thermophilic microorganisms such as Thermotoga maritima, Fervidobacterium nodosum and Ruminiclostridium thermocellum sharing 30-40% amino acid sequence identity. The molecular weight of the enzyme was determined as 40.5 kDa. Biochemical analyses revealed that the enzyme displayed good activity with soluble forms of cellulose as a substrate such as ostazin brilliant red hydroxyethyl cellulose (OBR-HEC), carboxymethylcellulose (CMC), hydroxyethyl cellulose (HEC) and insoluble azurine cross-linked hydroxyethylcellulose (AZCL-HEC). The enzyme shows highest enzymatic activity at pH 6.5 with high pH tolerance, remaining stable in the pH range 4.5 – 8.5. Highest activity was observed at 40 ˚C, but CelRH5 is psychrotolerant being active and stable at temperatures below 30 ˚C. The presence of final products of cellulose hydrolysis (glucose and cellobiose) or metal ions such as Na+, K+, Li+ and Mg2+, as well as ethylenediaminetetraacetic acid (EDTA), urea, dithiothreitol (DTT), dimethyl sulfoxide (DMSO), 2-mercaptoethanol (2-ME) or glycerol, did not have a marked effect on CelRH5 activity. However, the enzyme is quite sensitive in presence of 10 mM ions Zn2+, Ni2+, Co2+, Fe3+ and reagents such as 1 M guanidine HCl, 0.1% sodium dodecyl sulphate (SDS) and 20% ethanol. Given that it is psychrotolerant and retains activity in the presence of final cellulose degradation products, metal ions and various reagents, which are common in many technological processes; CelRH5 may be potential suitability for a variety of different biotechnological applications.